Preliminary exploration of the clinical features of Chinese patients with skin malignancies and premalignancies: a retrospective study of 1420 cases from Peking University First Hospital. (7th August 2012) - Huang, Y.S.; Chen, X.X.; Yang, S.X.; Wu, L.S.; Zhao, J.Y.; Li, X.Y.; Tu, P.; Li, H.
Abstract: Background  The epidemiological and clinical characterization data of skin malignancies and premalignancies in Chinese population is scarce and inadequate. Objective  To systematically investigate the clinical features and the trend of skin malignancies and premalignancies in 1420 Chinese cases. Methods  A total of 1398 patients (presenting 1420 skin tumours) were included. Clinical and demographic information for every individual was collected, including age, age of onset, sex, lesion location, disease duration and tumour histology, which was analyzed for each type of skin tumours. Results  The number of skin malignancies and premalignancies increased over time, with Basal cell carcinoma (BCC) as the most common type (30.5%). The majority of the patients were above 60 years of age both at onset and at diagnosis (52.8% and 62.9%, respectively), yet around one‐third of patients were between 35–59 years (35.3% and 31.2%, respectively). Skin malignancies and premalignancies were mainly located in the head and neck (58.6%), followed by the trunk (18.3%) and the extremities (15.0%). Of all BCCs, nodular BCC was the most common histologic subtype (62.8%), while 15.8% were classified as aggressive subtypes. Malignant melanoma (MM) comprised the lowest proportion of 3.7%, with 75% located on extremities. The diagnostic accordance rates varied from 49.5% to 90.4%, with BCC being 67.9%. Conclusions  The clinical features of skin malignancies and premalignancies in this study showed some similarities with those observed in Caucasian and other Asian populations, with several distinguished features in Chinese patients also being recognized. Closer attention to suspicious lesions in young and middle‐aged people is needed.